1976
DOI: 10.2136/sssaj1976.03615995004000060028x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Soil Properties as it Relates to the Genesis of Volcanic Ash Soils in Costa Rica

Abstract: Five soil profiles developed on andesitic volcanic ash, under welldrained conditions and at various elevations associated with different climatic conditions, were studied.These soils varied in profile development and degree of weathering from Incipient Ando soil (Umbric Vitrandept), Mature Ando soil (Typic Dystrandept), and Senile Ando soil (Hydric Dystrandept) to Incipient Latosol (Typic Humitropept) and Mature Latosol (Typic Palehumult).Profile development associated with time of ash deposition and climate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, it makes sense if different durations of pedogenesis are assumed. It has been shown in a number of studies that Andosols are formed on recent volcanic sediments whereas evolution towards soils with clay illuviation takes place on older landsurfaces (Martini, 1976;Delvaux et al, 1989). The fact that Luvisols of PT5-PT7 have more crystalline clay and less amorphous compounds (which is proved by anisotropism of clay in thin-sections and low quantities of Fe o , Al o and Si o ) fits well with our interpretation.…”
Section: Pedogenetic and Palaeoenvironmental Interpretation Of Palaeosupporting
confidence: 90%
See 1 more Smart Citation
“…However, it makes sense if different durations of pedogenesis are assumed. It has been shown in a number of studies that Andosols are formed on recent volcanic sediments whereas evolution towards soils with clay illuviation takes place on older landsurfaces (Martini, 1976;Delvaux et al, 1989). The fact that Luvisols of PT5-PT7 have more crystalline clay and less amorphous compounds (which is proved by anisotropism of clay in thin-sections and low quantities of Fe o , Al o and Si o ) fits well with our interpretation.…”
Section: Pedogenetic and Palaeoenvironmental Interpretation Of Palaeosupporting
confidence: 90%
“…However, soils derived from volcanic materials are known to differ considerably when formed under different environmental conditions (Mizota and van Reeuwijk, 1989). The correlation between Andosol properties and soil forming factors, especially climate and time (which is necessary for palaeoclimatic deductions), is available from a number of Andosol climo-and chronosequences in the tropics (Martini, 1976;Quantin, 1985;Nizeyimana, 1997). Detailed research on Andosols of the Sierra Nevada (central Mexico) also has been carried out by Mielich (1992).…”
Section: Introductionmentioning
confidence: 99%
“…Variation of depth to bedrock and other characteristics of volcanic ash soils have been investigated along landscape toposequences in many areas; most encompass a broad altitudinal range, yet include few profiles. Martini (1976) studied 5 soil profiles developed on andesitic ash at 790-2880 m on Irazú volcano (Costa Rica). Zehetner et al (2003) reported on 12 profiles formed on recent ash deposits at 2410-4050 m on Cotacachi volcano (Ecuador).…”
Section: Volcanic Ash Soil Toposequences and Measurement Of Soil Depthmentioning
confidence: 99%
“…Tile-probe penetration (Meyer et al, 2007) has proven inaccurate for depths b50 cm. Traditional excavation pits (Martini, 1976) involve arduous fieldwork and introduce significant soil disturbance, therefore are not advisable -or even permitted -in protected areas. Refraction seismic methods have been utilized with success (Meyer et al, 2007), but the costly equipment needed is not ideally suited for fieldwork in remote locations.…”
Section: Volcanic Ash Soil Toposequences and Measurement Of Soil Depthmentioning
confidence: 99%
“…In drier conditions on the lower slopes of the same volcano, Mollisols (dark soils of grasslands) and Alfisols (with clay-enriched subsoils; of medium to high base saturation), respectively, occur where soils are more base rich and where layer clays have been eluviated to give distinct argillic horizons. A shift toward layered clay minerals is associated with transition to these and other orders in tropical mountains: for example, Inceptisols and Ultisols (acid, highly weathered soils with eluviated clay, formed on old land surfaces) in Costa Rica (Martini 1976) and Cameroon (Delvaux et al 1989); Mollisols in the Rwandan highlands (Mizota & Chapelle 1988); Mollisols, Vertisols and Oxisols (known by many other names, including red latosols and tropical red earths) in Kenya (Wielemaker & Wakatsuki 1984) and soils described as Latosolic Andosols in Papua New Guinea (Haantjens et al 1967).…”
Section: Profile Morphology Of Soils In Tephramentioning
confidence: 99%